Editorial - Santini, Elio José (Ciência Florestal, 1999)
The Center of Forestry Research- CEPEF- is linked to the Fundação de Apoio à Tecnologia e Ciência (FATEC), of the Universidade Federal de Santa Maria, and was created in 1986 with the mission of promoting the scientific investigation, contributing to the solution of the unique problems of the forestry enterprise. For the publication of the technical-scientific knowledge generated in the Institution, and by other researchers in forestry, the Revista Ciência Florestal was created, in 1991, as a result of the combined effort between the University and the private forest sector. The difficulties found in the early number were slowly overcome, with the effective participation of all segments, always looking of the improvement of the scientific and editorial quality, compartible with the qualitative growth goals of the journal. In this context, the incorporation of nationally renown researchers to the editorial board turned the scientific consulting more selective. The first important recognition of this journal happened with its indexing by the CAB International System, from England, in 1997. The repercussion of the inclusion on the indexing system was felt by the significant increase in the number of manuscripts received. To meet this new challenge, and the demand by the Braxilian scientific community, the Editorial Board decided to implement a second number of the journal, making it biannual this year. Thus, the edition of the ninth volume will comprise this first number, in the month of June, and a second one, planned forDecember 1999. Another change, to catch your eyes, is the cover of the Journal, bringing a new style. The design was developed by the Visual Programming Laboratory, of the Center for the Arts and Literature od the UFSM, substantially changing its layout, and giving it a more modern and actual appeal. The innovation will be complemented by a different picture in each volume. CEPEF hopes to modernize its Journal of scientific publication with the new changes, adapting it to expectations of the readers. Although there are hurdles present at each edition, we hope to continue publishing scientific papers related to the Forest Sciences, giving ample access of the quality escientific knowledge to the readers of this journal.